2008
DOI: 10.1007/s10350-008-9213-8
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Povidone-Iodine Solution in Colorectal Operations: Science or Legend

Abstract: Povidone-iodine solution (Betadine) has long been accepted as an effective topical broad spectrum antiseptic, disinfectant, and tumoricidal agent. In colorectal operations, this solution generally has been used for the purpose of minimizing postoperative septic complications and reducing cancer recurrence, although the optimal application, advantages, and undesirable side effects have been debated. With limited prospective, randomized, controlled trials and insufficient data available, this article examines th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 71 publications
1
20
1
Order By: Relevance
“…This systematic review provides evidence that irrigation with PVI may reduce wound infection following elective colorectal operations. This finding is in disagreement with a recent narrative review [6]. The narrative review states that there is no conclusive evidence to support PVI; however, the authors did not perform a meta-analysis.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…This systematic review provides evidence that irrigation with PVI may reduce wound infection following elective colorectal operations. This finding is in disagreement with a recent narrative review [6]. The narrative review states that there is no conclusive evidence to support PVI; however, the authors did not perform a meta-analysis.…”
Section: Discussioncontrasting
confidence: 64%
“…The first article was removed because it was a narrative review on PVI in colorectal operations [6]. A second article was excluded due to lack of a control group, thus not meeting our criteria for a RCT [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some Authors reported the utility of PVI in reducing the bacterial concentration in colon mucosa [7]. A recent review from the Mayo Clinic was sceptical about PVI usefulness in colon surgery, nevertheless the authors concluded that in the acute setting peritoneal or wound irrigation with PVI may be useful in dirty or contaminated operations [8]. It has been suggested that Sodium Hypochlorite is more active on E. coli than PVI [9], but its use should be avoided as it is associated with higher rate of complications [7-10].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, instillation of cytotoxic agents such as povidone-iodine into the colon lumen is performed to decrease local recurrence. While detection of exfoliated viable tumour cells in the peritoneal cavity and the colon lumen proximal and distal to the tumour is a known phenomenon, we are lacking strong clinical evidence for any preventive effect of the above-mentioned techniques in terms of reduction of local or distant recurrence [11][12][13][14]. What has been shown to have a strong impact on recurrence and long-term outcome is the experience of the surgeon and institution as could be demonstrated by the German Colorectal Study Group.…”
Section: Surgical Strategy and Technical Aspectsmentioning
confidence: 99%